New media communication skills for engineers and IT professionals trans-national and trans-cultural demands - Patil, Arun S.; Eijkman, Henk, 1948-; Bhattacharyya, Ena, 1966-; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2012)
"This book provides new and experienced practitioners, academics, employers, researchers and students, with international examples of best practices in new as well as traditional communication skills in increasingly trans-cultural, digitalized, hypertext environments"--Provided by publisher.
1. Megatrends in engineering and technology education: a call for the communicative imagination / Arun Patil, and Henk Eijkman -- 2. 21st century education technologies for engineers and IT professionals / Chan Chang Tik -- 3. Enculturation into engineering professional practice: using legitimate peripheral participation to develop communication skills in engineering students / Richard K. Coll and Karsten E. Zegwaard -- 4. Communication framework to empower 21st century engineers and IT professionals / Ambigapathy Pandian, Shaik Abdul Malik Mohamed Ismail, and Ahmad Sofwan Nathan Abdullah -- 5. Linguistic and cultural skills for communication in global workplaces of the 21st century / Carmela Briguglio -- 6. Conceptual mapping, visualisation, and systems thinking in engineering / Carol Russell -- 7. Embedding communication skills in the study of the discipline / Katrina Falkner -- 8. Engineering students' self-perceived communication competence and technical presentation anxiety: a case study / Noor Raha Mohd Radzuan and Sarjit Kaur -- 9. Educating the 21st century's engineers and IT professionals / Antonios Andreatos -- 10. Multiple dimensions of media communication skills: new demands for transnational, trans-cultural knowledge exchange / Michael Singh and Guihua Cui -- 11. Visualization skills in engineering education: issues, developments, and enhancement / Dayana Farzeeha Ali, Arun Patil, and Mohd Safarin Nordin -- 12. Mitigation of communication challenges in the Indian software industry / Anjanee Sethi and Shyamli Rathore.
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed 2/21/2012).
Keywords: Communication in engineering; Engineering -- Vocational guidance; Information technology -- Vocational guidance; Engineering education technologies; Communication frameworks; Linguistic and cultural skills; Conceptual mapping; Systems thinking; Communication competence; Technical presentation anxiety; Transnational knowledge exchange; Trans-cultural knowledge exchange; Visualization skills; Electronic books